Learning beliefs and autonomous language learning with technology beyond the classroom - Lai, Chun (Language awareness, 2019)
Out-of-class exposure to and use of the target language mediated by technological resources are essential to language learning, as foreign language learners very often encounter difficulty in accessing and processing target language in the immediate physical environments. Understanding how foreign language learners' out-of-class self-directed technology-enhanced language learning experience interacts with their learning beliefs helps inform educators of how these learners could be supported to take advantage of technological resources to enrich language learning. Interview responses from 20 undergraduate foreign language learners at a university in Hong Kong were elicited to shed light on the issue. It was found that learners' language learning beliefs and technological behaviors had a two-way cyclical interaction, and the interaction was manifested in both the nature of technological resources these learners used and the way they interacted with the resources. Furthermore, the interaction between the two was context-dependent and subject to the influence of the characteristics of self-directed out-of-class technology-enhanced language learning and associated self-concept and affective factors. The study calls for a contextualized and systemic approach towards supporting foreign language learners' autonomous technology-enhanced language learning beyond the classroom.